La Logique Transactionnelle De L’appropriation Des Biens : Un Regard Sur La Structure Des Communes Camerounaises: The Transactional Logic of the Ownership of Goods: A Look at the Structure of Cameroonian Municipalities - Aurélien Bertrand, BOOK NYOBE; Noé, NDJECK (International Journal of Scientific Research and Management (IJSRM), 2022)
In the economic literature, it has been shown that the attributes of transactions impact the structure of organizations. However, the effects of the appropriation of communal land and forest are less well known. The study carried out in 36 municipalities and supported by a discreet analysis of transaction costs, shows that depending on the degree of specificity of the asset, the regulated management and the management in interested party would impact the financial structure. This would help improve revenues, in taking into account externalities and risk.